2012
DOI: 10.3109/08977194.2011.649918
|View full text |Cite
|
Sign up to set email alerts
|

EGFR ligands exhibit functional differences in models of paracrine and autocrine signaling

Abstract: Epidermal growth factor (EGF) family peptides are ligands for the EGF receptor (EGFR). Here, we elucidate functional differences among EGFR ligands and mechanisms underlying these distinctions. In 32D/EGFR myeloid and MCF10A breast cells, soluble amphiregulin (AR), transforming growth factor alpha (TGFα), neuregulin 2 beta, and epigen stimulate greater EGFR coupling to cell proliferation and DNA synthesis than do EGF, betacellulin, heparin-binding EGF-like growth factor, and epiregulin. EGF competitively antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 32 publications
3
99
0
Order By: Relevance
“…EGF, b-cellulin (BTC), heparin-binding EGF-like growth factor (HB-EGF), and TGFa are high-affinity ligands with binding affinity (K D ) of 0.6 to 9.2 nmol/L, whereas amphiregulin (AREG), epiregulin (EREG), and epigen (EPI) are considered low-affinity ligands with K D of 350 nmol/L to 2.8 mmol/L (6, 7). EGFR ligands exhibit different signaling intensities, durations, and trafficking, resulting in differential EGFR signaling and physiologic consequences (8)(9)(10). AREG and EREG are EGFR ligands that are predominantly expressed in CRC cell lines (11).…”
Section: Introductionmentioning
confidence: 99%
“…EGF, b-cellulin (BTC), heparin-binding EGF-like growth factor (HB-EGF), and TGFa are high-affinity ligands with binding affinity (K D ) of 0.6 to 9.2 nmol/L, whereas amphiregulin (AREG), epiregulin (EREG), and epigen (EPI) are considered low-affinity ligands with K D of 350 nmol/L to 2.8 mmol/L (6, 7). EGFR ligands exhibit different signaling intensities, durations, and trafficking, resulting in differential EGFR signaling and physiologic consequences (8)(9)(10). AREG and EREG are EGFR ligands that are predominantly expressed in CRC cell lines (11).…”
Section: Introductionmentioning
confidence: 99%
“…infected mice at 12 h demonstrated that the host transcriptional response at 12 h of infection was predominantly proinflammatory; for example, amphiregulin (AREG) (20)(21)(22), a potent activator of the epidermal growth factor receptor (EGFR) which is transactivated by LEPR, and CD47 (23) and CD38 (24) were induced (25). Ingenuity pathway analysis (IPA) indicated enrichment of gene functions involved in cell-to-cell signaling and interaction and in cellular function and maintenance, with immune cells being especially targeted (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…For example, TGFα and AREG stimulate proliferation of 32D cells more efficiently than do EGF and HB-EGF, and these efficiency differences have been correlated with differential phosphorylation of specific sites on the Cterminal tail of EGFR [90][91][92]. This is partly due to different binding affinities of the distinct ligands for EGFR [93,94].…”
Section: Mechanism Of Activation Of Egfr Dimers By Ligand Binding: Thmentioning
confidence: 96%